The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.33369/joall.v7i1.18724
|View full text |Cite
|
Sign up to set email alerts
|

Improving EFL ninth graders’ reading comprehension through thieves learning strategy

Abstract: Reading as a fundamental language skill become an essential skill in academic and social life. Especially at school, the teachers need to enrich the strategy in teaching and learning process. The objectives of this study were to find out 1) the improvement of students’ reading comprehension of the ninth grade (IXC) of SMPN 13 North Bengkulu, 2) some factors influence the change of students’ reading comprehension at the ninth grade (IX C) of SMPN 13 North Bengkulu. This Classroom Action Research (CAR) involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…They also added that THIEVES Strategy makes the learning process easy, builds extensive knowledge, helps connect and predict the text by the clues that are found through the text, and effectively improves student's reading comprehension. Moreover, THIEVES strategy is applicable to any sort of literature in comparison to other reading strategies (Asmarni et al, 2022). It could be used in nonfiction text including diaries, letters, advertising and propaganda, explanation, descriptions, instructions, tables, forms, reports, arguments, notice and signs, catalogs and directories (Gusvianti & Tiarina, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…They also added that THIEVES Strategy makes the learning process easy, builds extensive knowledge, helps connect and predict the text by the clues that are found through the text, and effectively improves student's reading comprehension. Moreover, THIEVES strategy is applicable to any sort of literature in comparison to other reading strategies (Asmarni et al, 2022). It could be used in nonfiction text including diaries, letters, advertising and propaganda, explanation, descriptions, instructions, tables, forms, reports, arguments, notice and signs, catalogs and directories (Gusvianti & Tiarina, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In line with the previous studies, Khataee (2019) who used expository text concluded that this strategy could assist students in overcoming challenges such as insufficient language knowledge, time constraints, and difficult or unfamiliar topics. Similarly, Asmarni et al (2022), who utilized narrative and report text, highlighted that the strategy can enhance student engagement and learning in the teaching learning process.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations